Effects of terrestrial and marine organic matters on deposition of dechlorane plus (DP) in marine sediments from the Southern Yellow Sea, China: Evidence from multiple biomarkers. (November 2017) - Wang, Guoguang; Peng, Jialin; Hao, Ting; Feng, Lijuan; Liu, Qiaoling; Li, Xianguo
Abstract: As an emerging halogenated organic contaminant, Dechlorane Plus (DP) was scarcely reported in marine environments, especially in China. In this work, 35 surface sediments and a sediment core were collected across the Southern Yellow Sea (SYS) to comprehensively explore the spatio-temporal distribution and possible migration pathway of DP. DP concentrations ranged from 14.3 to 245.5 pg/g dry weight in the surface sediments, displaying a seaward increasing trend with the high levels in the central mud zone. This spatial distribution pattern was ascribed to that fine particles with the elevated DP levels were preferentially transported to the central mud zone under hydrodynamic forcing and/or via long-range atmospheric transportation and deposition. DP concentrations in sediment core gradually increased from the mid-1950s to present, which corresponded well with the historical production and usage of DP, as well as the economic development in China. Significantly positive correlation between DP and total organic carbon (TOC) in both surface sediments and sediment core indicated TOC-dependent natural deposition of DP in the SYS. We used multiple biomarkers, for the first time, to explore the potential effects of terrestrial and marine organic matters (TOM and MOM) on DP deposition. The results showed that competition may occur between TOM and MOM for DP adsorption, and MOM was the predominant contributor in controlling DP deposition in the marine sediments from the SYS. Graphical abstract: Highlights: Effects of TOM and MOM on DP deposition were first explored by multi-biomarkers. Hydrodynamic forcing and atmospheric deposition were responsible for DP in the SYS. MOM was the predominant contributor in controlling DP deposition to sediments in the SYS. Competition may occur between TOM and MOM for DP adsorption. Abstract : This study was the first attempt to comprehensively explore the effects of TOM and MOM on DP deposition in marine sediments from the SYS.